Pathophysiologic Basis of Haemolysis in Patients with Sickle Cell Disease in Steady State and in Hyperhaemolytic States - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Sickle cell disease (SCD) is characterized by red cell sickling, tissue infarcts, pain and haemolysis. Haemolysis leads to anaemia, transfusion and vasculopathic multi-organ damage (VMOD). Every SCD patient maintains a chronic steady state haemolysis (SSH), which is often aggravated to hyperhaemolysis (HH) by inherited and/or acquired comorbidities. Hence, this article aims to present an updated and comprehensive narrative literature review of aetiopathogenesis, management and mitigation of SCD haemolysis in steady state and in various hyperhaemolytic states. Literature search revealed SSH is initiated by steady state sickling due to tissue hypoxia and is driven by lactic acidemia, Bohr effect, low pyruvate kinase activity, reduced oxygen affinity of HbS, lipid peroxidation, eryptosis, senescence antigen expression, Fc-receptor or ligand mediated erythro-phagocytosis, xanthine oxidase (XO) hyperactivity and intravascular red cells lysis. SSH is often aggravated to chronic or acute HH by various acquired and/or inherited haemolytic comorbidities such as G6PD deficiency, hereditary spherocytosis (HS), acute/chronic hypersplenic or acute hepatic sequestration, infective erythrocytotropism and erythrocytopathy, haemophagocytic syndrome, transfusion reaction, alloimmune, autoimmune and drug-induced haemolysis. While transfusion provides short-term solution for severe haemolysis and anaemia in SCD, long-term solution must include mitigation of haemolysis by using HbF enhancers, HbS oxygen affinity modifiers, XO inhibitors, immune modulators for immune-haemolysis, use of anti-oxidants to minimize peroxidation, avoidance of oxidants if patient is also G6PD deficient, administering antibiotics/vaccinations to treat/prevent infections, splenectomy for comorbid HS or any recalcitrant hypersplenic splenomegaly. This narrative review underscores importance of managing SSH and HH in order to alleviate anaemia, minimize transfusion, and prevent VMOD in SCD.